Flow chemistry : integrated approaches for practical applications - Luis, S. V. (Santíago V.); García-Verdugo, E. (Eduardo) (Cambridge : Royal Society of Chemistry, 2020)
This volume provides an update on recent advances in the field of flow chemistry, with emphasis on new, integrated approaches for green and efficient chemistry.
Recent Perspectives in Catalysis under Continuous Flow / Haruro Ishitani, Yuki Saito, Benjamin Laroche, Xiaofeng Rao and Shu¯ Kobayashi -- Green Biotransformations under Flow Conditions / Eduardo Garcia-Verdugo, Rau´l Porcar, Santiago V. Luis and Pedro Lozano -- Organometallic Chemistry in Flow in the Pharmaceutical Industry / E. Palao and J. Alcazar -- Perspectives on the Use of Flow Systems to Carry Out Organic Photochemical Reactions / K. Mizuno and K. Kakiuchi -- Electrochemistry under Flow Conditions / Ana A. Folgueiras-Amador and T. Wirth -- Sustainable Approaches to C-H Functionalizations Through Flow Techniques / S. Santoro, F. Ferlin and L. Vaccaro -- Radical Polymerisation under Flow Conditions / Laurens Brocken and Ian R. Baxendale -- Ionic Polymerisation and New Approaches to Polymerisation under Flow Conditions / Laurens Brocken and Ian R. Baxendale -- Continuous Flow Synthesis of Nanomaterials / Amol A. Kulkarni and Rajashri B. Jundale -- NMR Microcoils for On-line Reaction Monitoring / M. V. Gomez and A. H. Velders -- Flow Chemistry Systems Based on Membranes / J. Sanchez-Marcano -- New Microreactor Designs for Practical Applications Realized by Additive Manufacturing / P. Lo¨b -- Additively Manufactured Advanced Flow Reactors for Enhanced Heat and Mass Transfer / Obinna Okafor, Ruth Goodridge and Victor Sans -- Integrated Microreaction Systems of Microdevices with Conventional Equipment / G. S. Luo, J. Deng and K. Wang -- Automation of Flow Chemistry / Jonathan N. Jaworski, Rachel L. Beingessner and Timothy F. Jamison -- Upscaling the Aza-Diels-Alder Reaction for Pharmaceutical Industrial Needs in Flow Chemistry / G. Pascual-Coca, F. Tato, J. F. Soriano and R. Ferritto-Crespo -- Industrial Continuous-flow Chemistry under cGMP Conditions / Robert Moylan, Sharon Bourke, Kevin Cole and Scott May.
Online resource; title from PDF title page (EBSCO, viewed October 2, 2019)
Includes index.
eBooks on EBSCOhost
Keywords: Flow chemistry; Green chemistry; Chimie en flux continu; Chimie verte; Flow chemistry; Green chemistry